2004
DOI: 10.1210/en.2004-0959
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: Cyclin D1: Normal and Abnormal Functions

Abstract: Cyclin D1 encodes the regulatory subunit of a holoenzyme that phosphorylates and inactivates the retinoblastoma protein and promotes progression through the G1-S phase of the cell cycle. Amplification or overexpression of cyclin D1 plays pivotal roles in the development of a subset of human cancers including parathyroid adenoma, breast cancer, colon cancer, lymphoma, melanoma, and prostate cancer. Of the three D-type cyclins, each of which binds cyclin-dependent kinase (CDK), it is cyclin D1 overexpression tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
766
1
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 866 publications
(804 citation statements)
references
References 114 publications
(140 reference statements)
26
766
1
11
Order By: Relevance
“…Cyclin D1 also exhibits CDK-independent activities that influence apoptotic pathways, cellular migration, and angiogenesis all of which may be important in the neoplastic context. [10][11][12]16 Over-expression of cyclin D1 has been documented in diverse neoplasms including breast carcinoma, head and neck squamous carcinoma, parathyroid adenoma and mantle cell lymphoma, and some studies have shown a correlation between increased cyclin D1 and adverse prognosis. Therefore, our observation that cyclin D1 immunoreactivity was usually lost in neoplastic endocervical lesions seemed to be a counter-intuitive finding, particularly as such lesions are known to show prominent mitotic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclin D1 also exhibits CDK-independent activities that influence apoptotic pathways, cellular migration, and angiogenesis all of which may be important in the neoplastic context. [10][11][12]16 Over-expression of cyclin D1 has been documented in diverse neoplasms including breast carcinoma, head and neck squamous carcinoma, parathyroid adenoma and mantle cell lymphoma, and some studies have shown a correlation between increased cyclin D1 and adverse prognosis. Therefore, our observation that cyclin D1 immunoreactivity was usually lost in neoplastic endocervical lesions seemed to be a counter-intuitive finding, particularly as such lesions are known to show prominent mitotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many tumors exhibit abnormalities within the RB-p16-cyclin D1 pathways, and often these lead to increased activity of cyclin D1. [10][11][12] However, we have noted in routine practice that adenocarcinoma in situ and invasive cervical adenocarcinoma usually lack expression of cyclin D1, whereas the nuclei of most normal endocervical epithelial cells are positively stained. This seems a surprising finding as neoplastic endocervical lesions are typically characterized by prominent mitotic activity and show increased expression of the proliferationassociated marker Ki-67/MIB-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bars: 50 Îźm Prolonged upregulation of cyclin D1, a rate-limiting cell cycle protein, after PH is required for adequate LR. 19 Figure 1), but did increase in a delayed fashion (7 d) in HET mice that survived PH. Altogether these data indicate that hepatocyte proliferation post PH is aborted and/or delayed in A20 HET livers.…”
mentioning
confidence: 90%
“…Second, cyclin D1 can associate with histone deacetylases to repress transcription, and this function of cyclin D1 is essential for its AR corepressor activity Petre-Draviam et al, 2005). Cyclin D1 can also bind to and modulate other transcription factors by similar mechanisms, with the largest class of proteins belonging to the nuclear receptor superfamily (Coqueret, 2002;Ewen and Lamb, 2004;Fu et al, 2004). These collective observations have culminated in a model whereby androgen-mediated induction of cyclin D1 serves to activate CDK4 and promote cell cycle progression, but that accumulated cyclin D1 engages in a negative feedback loop to limit or modulate the response to androgen stimulation.…”
mentioning
confidence: 99%